Luz e experimentação no retrato fotográfico - Muniz, Deborah Araújo (2016)
This study aims to investigate the expressive use of light and experimentation in the artistic composition of the photographic portrait. It is considered in this research the photographic composition thought to the light, as an aesthetic element responsible for setting up what is put in and create perceptions in the picture, based on the concept that to portray a certain subject, the photographer proposes express it somehow, you think of an idea of lighting that produces the atmosphere and the desired expressive effect. The light is manifested in the picture in different ways, according to the principles of subjective composition, corresponding to what the photographer wants to express what portrays. Combined with experimental activity in the photographic composition, experimentation implies an act of discovery and creation inherent in choices that lead to materialization of artistic expression in the picture. It is through the photographic writing photographers create their images. In this sense, the study examines the artistic composition of pictures produced by Camila hose and Tiago Santana, lighting and experimental activity as ways to shape the photographic portrait. The methodological design is literature, descriptive and exploratory research. Found that the lighting is a power capable of producing extraordinary effects on the image, creating different atmospheres and be responsible for the expressiveness of the image, manifesting the image through the light elements and shadow, its color, its direction, its intensity, its character in interaction with other frame elements, through experimental manipulation, stress characteristics of the portrait subject and attribute meanings suggestive and evocative to portraying.